Sub-kilometer dynamical downscaling of near-surface winds in complex terrain using WRF and MM5 mesoscale models - Horvath, Kristian; Koracin, Darko; Vellore, Ramesh; Jiang, Jinhua; Belu, Radian (Journal of Geophysical Research: Atmospheres, 2012)
Sub‐kilometer dynamical downscaling was performed using the Weather Research and Forecasting (WRF) and Mesoscale Model Version 5 (MM5) models. The models were configured with horizontal grid spacing ranging from 27 km in the outermost telescoping to 333 m in the innermost domains and verified with observations collected at four 50‐m towers in west‐central Nevada during July and December 2007. Moment‐based and spectral verification metrics showed that the performance of WRF was superior to MM5. The modeling results were more accurate at 50 m than at 10 m AGL. Both models accurately simulated the mean near‐surface wind shear; however, WRF (MM5) generally overestimated (underestimated) mean wind speeds at these levels. The dispersion errors were the dominant component of the root‐mean square errors. The major weakness of WRF was the overestimation of the intensity and frequency of strong nocturnal thermally driven flows and their sub‐diurnal scale variability, while the main weaknesses of MM5 were larger biases, underestimation of the frequency of stronger daytime winds in the mixed layer and underestimation of the observed spectral kinetic energy of the major energy‐containing motions. Neither of the verification metrics showed systematic improvement in the models' accuracy with increasing the horizontal resolution and the share of dispersion errors increased with increased resolution. However, a profound improvement in the moment‐based accuracy was found for the mean vertical wind shear and the temporal variability of wind speed, in particular for summer daytime simulations of the thermally driven flows. The most prominent spectral accuracy improvement among the primary energy‐containing frequency bands was found for both models in the summertime diurnal periods. Also, the improvement for WRF (MM5) was more (less) apparent for longer‐than‐diurnal than for sub‐diurnal periods. Finally, the study shows that at least near‐kilometer horizontal grid spacing is necessary for dynamical downscaling of near‐surface wind speed climate over complex terrain; however, some of the physics options might be less appropriate for grid spacing nearing the scales of the energy‐containing turbulent eddies, i.e., resolutions of several hundred meters. In addition to the effects of the lower boundary, the accuracy of the lateral boundary conditions of the parent domains also controls the onset and evolution of the thermally driven flows. Key Points WRF performance is superior to MM5; model error is higher closer to the ground The improvement with horizontal grid resolution is not systematic The most profound improvement was found for wind shear and bias of std. dev